Genomic analysis of Bacillus subtilis lytic bacteriophage ϕNIT1 capable of obstructing natto fermentation carrying genes for the capsule-lytic soluble enzymes poly-γ-glutamate hydrolase and levanase. Issue 1 (2nd January 2017) - Ozaki, Tatsuro; Abe, Naoki; Kimura, Keitarou; Suzuki, Atsuto; Kaneko, Jun
Abstract: Bacillus subtilis strains including the fermented soybean (natto) starter produce capsular polymers consisting of poly-γ-glutamate and levan. Capsular polymers may protect the cells from phage infection. However, bacteriophage ϕNIT1 carries a γ-PGA hydrolase gene ( pghP ) that help it to counteract the host cell's protection strategy. ϕNIT had a linear double stranded DNA genome of 155, 631-bp with a terminal redundancy of 5, 103-bp, containing a gene encoding an active levan hydrolase. These capsule-lytic enzyme genes were located in the possible foreign gene cluster regions between central core and terminal redundant regions, and were expressed at the late phase of the phage lytic cycle. All tested natto origin Spounavirinae phages carried both genes for capsule degrading enzymes similar to ϕNIT1. A comparative genomic analysis revealed the diversity among ϕNIT1 and Bacillus phages carrying pghP -like and levan-hydrolase genes, and provides novel understanding on the acquisition mechanism of these enzymatic genes. Graphical abstract: :